Proteomics and metabolomics reveal the mechanism underlying differential antioxidant activity among the organs of two base plants of Shiliang tea (Chimonanthus salicifolius and Chimonanthus zhejiangensis). (15th August 2022) - Yang, Bingxian; Li, Qi; Cheng, Kaisen; Fang, Jie; Mustafa, Ghazala; Pan, Junjie; Xing, Bingcong; Lv, Qundan; Zhang, Lin; Cheng, Kejun
Graphical abstract: Highlights: The antioxidant activity of branch is stronger than leaf in two species. The trypsin/protease inhibitor activity of branch is stronger than leaf. Flavonoids (phenylpropanoids)-related proteins were with higher abundance in branch. Isoprenoids-related proteins were with higher abundance in leaf. Procyanidins were more accumulated in branch than leaf in two species. Abstract: The leaves and branches of Chimonanthus salicifolius and Chimonanthus zhejiangensis are the base ingredients of Shiliang tea. In this study, proteomics and metabolomics were performed to understand the molecular mechanisms underlying antioxidant activity (AA) in the leaves and branches of the two species. Stress and redox related proteins are differentially expressed among organs. The abundance of isoprenoid pathway-related proteins is higher in leaves while the abundance of phenylpropanoid and flavonoid pathway-related proteins is higher in branches in both species. Metabolomics revealed the flavonoid composition and demonstrated that procyanidins are more abundant in branches. Superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and AA are stronger in branches than leaves. Overall, branches might contribute to redox homeostasis through SOD/GSH-PX and flavonoids. Furthermore, the high level of AA of branches might be largely due to their increased accumulation of procyanidins.